IAA content in relation to seed germination of oryza sativa / Nur Atiqah Abdul Halim - Abdul Halim, Nur Atiqah (Faculty of Plantation and Agrotechnology, 2018)
Paddy (Oryza sativa) is an annual grass of the Gramineae family. There are many varieties of paddy available in the market. It is the main source of food for about half of the world’s population, especially people in Asia. In this study, the selected varieties (MARDI Siraj 297) is a new variety of MARDI which is able to produce high yield, and has resistance to leaf disease, stalk and viral diseases as well as good flavour. Seed dormancy is common in Gramineae family. Dormancy mechanisms in seeds will control germination. There are several factors that contribute to dormant condition. One of them is because of high concentration of auxin, for example indole-3-acetic acid (IAA). Auxin is actually needed for seed germination but only in small quantity. The current study was aimed to determine the effect of water soaking period on IAA content in paddy endosperm and husk, percentage of germination and germination index. To evaluate the effect of soaking period on IAA content, different soaking periods of 0, 1 and 2 days were applied to paddy seeds. Germination test was used to assess the percentage of germination and germination index. Each treatment had five replicates. Each replicate contained 30 paddy seeds and were put in different Petri dishes for germination test. Daily observations were carried out for seven days. The results revealed that soaking for one day reduced IAA content in both endosperm and husk besides speed up the germination rate. The ultimate germination percentages as affected by soaking period were not significantly different (P>0.05) but germination index was higher with seeds soaked for one day. High IAA in seeds seemed an inhibitor to seed germination.